Europe, globalization and sustainable development - Barry, John, 1966-; Baxter, Brian, 1949-; Dunphy, Richard (Routledge research in environmental politics, 2004)
This edited volume considers the ways in which European states and the European Union can and should organize themselves economically and socially in order to address the challenges of sustainable development. It will interest students and researchers of environmental policy and European politics.